Impact of Cash Holding on Firm Performance with Moderating Role of Corporate Governance - Naveed Anjum; Dr. Faisal Khan; Shoib Hassan; Dr. Muhammad Arif (Journal of Business & Tourism, 2021)
The main aim of this research is to analyze the association between cashholding and firm performance with moderating role of corporate governance. For the purpose of analysis, secondary data of 145 non-financial firms listed at Pakistan Stock Exchange (PSX) is taken from 2006-2017. The dynamic Generalized Method of Moments (GMM) is applied to cater the problem of unobserved heterogeneity. The results of this study suggest that cash holding has a significant impact on firm performance. Moreover, corporate governance significantly moderates the relationship between cash holding and firm performance.